Analisis Perkembangan Kinerja Instrrument Pasar Modal Syariah: Reksa Dana Syariah Dan Saham Syariah Di Indonesia Periode 2010-2022 - Hasibuan, Zakia Hasanah; Zuhriadi, Muhammad Zuhriadi; sibarani, Juan charlos; Manurung, Reneva Manurung; Aruan, Nur Indah Melani; Hutagalung, Irma Hutagalung; Habeahan, Jaiton Habeahan (Maisyatuna, 2023)
The purpose of this study was to determine the development of the performance of Islamic capital market instruments, especially Islamic mutual funds and Islamic stocks in Indonesia, in the 2010-2022 timeframe. The analytical method used in this study is a qualitative descriptive analysis method with secondary data obtained by accessing publications issued by the Financial Services Authority (OJK) and the Central Bureau of Statistics (BPS). The population in this study are all companies listed on the Islamic Stock Index (ISSI) and the entire number of Islamic mutual funds during the observation period 2010 – 2022. The results of this study reveal that the development of the performance of Islamic mutual funds and Islamic stocks has increased quite significantly. With a deeper understanding, it is expected to be able to provide recommendations and actualize relevant policies to improve the performance of Islamic capital market instruments in the future.